Seasonal River Chemistry and Lithium Isotopes in the Min Jiang at Eastern Tibetan Plateau: Roles of Silicate Weathering and Hydrology - Liu-Lu, Baiyang; Jin, Zhangdong; Gou, Long-Fei; Zhang, Fei; He, Mao-Yong; Xu, Yang (Frontiers in Earth Science, 2022)
Riverine lithium (Li) isotopes have been considered as a robust tracer for silicate weathering, but processes controlling riverine Delta7Li ratio remain controversial. To address the impacts of weathering and hydrology on riverine Delta7Li, the seasonal variation of water chemistry in the Min Jiang at the eastern Tibetan Plateau was investigated over the year of 2010. The results showed distinct seasonal variations in ionic chemistry and Delta7Li. Increased river discharge in the monsoon season diluted dissolved ions, and monsoonal hydrological changes caused frequent Delta7Li fluctuation. High discharge by monsoonal rainfall reduced Li isotope fractionation owing to short rock-fluid interaction, resulting in lower Delta7Li. Meanwhile, the input of groundwater and/or landslide seepage with high Delta7Li during the monsoon season was considered to elevate riverine Delta7Li, together with increased residence time caused by decreased discharge in less rain intervals. Based on the high-resolution sampling strategy and dataset over one hydrological year, this study highlights that changes of hydrological conditions can have a significant impact on weathering processes and water sources and therefore on riverine Delta7Li variation.